Breast cancer with medullary features shows a fast and plateau enhancement pattern on magnetic resonance images: A case report - Senri Kondo; Shoji Oura; Mariko Honda (Radiology Case Reports)
An 80-year-old woman with a left breast mass was referred to our department. Mammography showed an oval mass, 2.5cm in size, with circumscribed margins in her left breast. Ultrasound showed an oval tumor with circumscribed margins, heterogenous internal echoes including numerous punctate hyperechoic foci, and posterior echo enhancement. Magnetic resonance imaging (MRI) of the tumor showed low and high signal intensity on T1-weighted images and on fat-suppressed T2-weighted images, respectively. Kinetic curve assessment of the tumor showed a fast and plateau pattern. After the pathological confirmation of malignant cells, the patient underwent mastectomy and sentinel node biopsy. Postoperative pathological study showed that atypical cells formed irregularly arranged papillary nests and grew in a medullary fashion accompanied by massive lymphocyte infiltration, leading to the diagnosis of invasive ductal carcinoma with medullary features (IDCMF). Immunostaining showed that the tumor had a triple negative phenotype and a high Ki-67 labelling index of 52%. In conclusion, breast diagnostic physicians should note that IDCsMF show a fast and plateau enhancement pattern on MRI kinetic curve assessment. Furthermore, the presence of punctate hyperechoic foci in the tumor can be useful in distinguishing IDCsMF from medullary breast carcinomas.